Patrones de Inserción de las Empresas Multinacionales en la Formación de Competencias Tecnológicas de Paises Seguidores - Ruiz, Ana Urraca (2009)
Using a database composed by patents filed in the European Patent Office, this paper aims to: (i ) identify patterns of technological specialization of selected countries from Latin America and Asia; (ii ) classify the role played by MNE (multinational enterprises) in the building of technological competencies of these countries as well as their role in the catching-up process. The paper concludes that: (i ) there are different patterns of specialization of MNE according to their level of participation in the technological structure of the host country and to the geographic region where the country is located; (ii ) MNE do not necessarily duplicate their homebased competencies, but may explore local specialization; and (iii ) MNE are more likely to favor diversification of technical base in Asian countries like India and Hong Kong and to deepen specialization in Latin American countries, such as Brazil and Argentina.